DOCK2 and phosphoinositide-3 kinase δ mediate two complementary signaling pathways for CXCR5-dependent B cell migration - Wissmann, Stefanie; Stolp, Bettina; Jímenez, Ana Marcos; Stein, Jens V. (Frontiers in Immunology, 2022)
Naive B cells use the chemokine receptor CXCR5 to enter B cell follicles, where they scan CXCL13-expressing ICAM-1+ VCAM-1+ follicular dendritic cells (FDCs) for the presence of antigen. CXCL13-CXCR5-mediated motility is mainly driven by the Rac guanine exchange factor DOCK2, which contains a binding domain for phosphoinositide-3,4,5-triphosphate (PIP3) and other phospholipids. While p110, the catalytic subunit of the class IA phosphoinositide-3-kinase (PI3K), contributes to CXCR5-mediated B cell migration, the precise interdependency of DOCK2, p110, or other PI3K family members during this process remains incompletely understood. Here, we combined in vitro chemotaxis assays and in vivo imaging to examine the contribution of these two factors during murine naïve B cell migration to CXCL13. Our data confirm that p110 is the main catalytic subunit mediating PI3K-dependent migration downstream CXCR5, whereas it does not contribute to chemotaxis triggered by CXCR4 or CCR7, two other chemokine receptors expressed on naïve B cells. The contribution of p110 activity to CXCR5-driven migration was complementary to that of DOCK2, and pharmacological or genetic interference with both pathways completely abrogated B cell chemotaxis to CXCL13. Intravital microscopy of control and gene-deficient B cells migrating on FDCs confirmed that lack of DOCK2 caused a profound migration defect, whereas p110 contributed to cell speed and directionality. B cells lacking active p110 also displayed defective adhesion to ICAM-1; yet, their migration impairment was maintained on ICAM-1-deficient FDCs. In sum, our data uncover two complementary signaling pathways mediated by DOCK2 and p110, which enable CXCR5-driven naïve B cell examination of FDCs.